2015
DOI: 10.1016/j.chom.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Toxoplasma Dense Granule Proteins GRA17 and GRA23 Mediate the Movement of Small Molecules between the Host and the Parasitophorous Vacuole

Abstract: Summary Toxoplasma gondii is a protozoan pathogen in the phylum Apicomplexa that resides within an intracellular parasitophorous vacuole (PV) that is selectively permeable to small molecules through unidentified mechanisms. We have identified GRA17 as a Toxoplasma-secreted protein that localizes to the parasitophorous vacuole membrane (PVM) and mediates passive transport of small molecules across the PVM. GRA17 is related to the putative Plasmodium translocon protein EXP2 and conserved across PV-residing Apico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(272 citation statements)
references
References 37 publications
11
251
1
9
Order By: Relevance
“…So far, no functional data are available for the predicted pore component EXP2 in P. falciparum. However, very recent data showed that PfEXP2 can complement the role of T. gondii GRA17, a related protein implicated in the long-sought nutrient pore activity of apicomplexan PVMs [64]. As one explanation for this finding, it was proposed that PfEXP2 may be a part of both a nutrient and a protein-conducting pore [64].…”
Section: Delivering Exported Proteins To the Host Cellmentioning
confidence: 99%
“…So far, no functional data are available for the predicted pore component EXP2 in P. falciparum. However, very recent data showed that PfEXP2 can complement the role of T. gondii GRA17, a related protein implicated in the long-sought nutrient pore activity of apicomplexan PVMs [64]. As one explanation for this finding, it was proposed that PfEXP2 may be a part of both a nutrient and a protein-conducting pore [64].…”
Section: Delivering Exported Proteins To the Host Cellmentioning
confidence: 99%
“…gondii tachyzoites reside within a unique, non-fusogenic parasitophorous vacuole within the host cell (Joiner et al, 1990) and have access to a variety of carbon sources that can permeate across the limiting membrane of the vacuole (Gold et al, 2015;Schwab et al, 1994). However, 13 C-labeling and genetic studies (Lin et al, 2011;MacRae et al, 2012;Ohsaka et al, 1982;Starnes et al, 2009) suggest that under normal growth conditions, intracellular tachyzoites primarily utilize glucose to generate energy and essential anabolic precursors via glycolysis, the pentose phosphate pathway, and mitochondrial respiration.…”
Section: Introductionmentioning
confidence: 99%
“…However, knockdown of the expression of GRA17 in T. gondii did not affect the export of GRA24 and the PEXEL-containing protein GRA16. Instead it led to a decrease in the movement of small molecules across the PVM 66 . Furthermore, membrane conductance was enhanced in Xenopus laevis oocytes in which GRA17 and EXP2 were overexpressed 66 , but the time that was required to alter the conductance was much longer than would be expected for proteins that have functions in pore formation.…”
Section: Maurer's Cleftsmentioning
confidence: 96%
“…The homologue in T. gondii, GRA17, seems to function as a nutrient pore and can be functionally substituted with EXP2 (REF. 66), which suggests that EXP2 may have been a nutrient pore in the ancestor of Plasmodium spp. before being repurposed as a protein channel following the recruitment of HSP101.…”
Section: Parasitophorous Vacuolementioning
confidence: 99%